1992
DOI: 10.1115/1.2899478
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Acoustic Pulses Reflected From Fiber-Reinforced Composite Laminates

Abstract: The time histories and spectral characteristics of acoustic pulses reflected from fiberreinforced composite laminates immersed in water are recorded in the laboratory and analyzed through a generalized ray theory and an exact theory. Calculated results for an unidirectional laminate and two angle-ply laminates are compared with measured data. It is shown that for a unidirectional laminate a finite number of mode-converted waves contribute to the overall signal reflected from a thick specimen resulting in certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In three dimensions, scattering by transversely isotropic cylinders is studied in Honarvar and Sinclair (1996) and Niklasson and Datta (1998) among others, while an extension of the methodology proposed in Honarvar and Sinclair (1996) to the case of a cylindrical shell is found in Kim and Ih (2003). Other examples of scattering problems involving transversely isotropic solids are Kundu and Boströ m (1992) and Mal et al (1992). On the other hand, when it comes to materials with a higher degree of anisotropy, the investigation of the wave propagation and scattering phenomena is based upon numerical methods such as the finite element method (FEM; Lord et al, 1990), the elastodynamic finite integration technique (EFIT; Fellinger et al, 1995), the boundary element method (BEM; Wang et al, 1996) and the strip element method (SEM; Liu and Achenbach, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…In three dimensions, scattering by transversely isotropic cylinders is studied in Honarvar and Sinclair (1996) and Niklasson and Datta (1998) among others, while an extension of the methodology proposed in Honarvar and Sinclair (1996) to the case of a cylindrical shell is found in Kim and Ih (2003). Other examples of scattering problems involving transversely isotropic solids are Kundu and Boströ m (1992) and Mal et al (1992). On the other hand, when it comes to materials with a higher degree of anisotropy, the investigation of the wave propagation and scattering phenomena is based upon numerical methods such as the finite element method (FEM; Lord et al, 1990), the elastodynamic finite integration technique (EFIT; Fellinger et al, 1995), the boundary element method (BEM; Wang et al, 1996) and the strip element method (SEM; Liu and Achenbach, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…A good understanding of Lamb wave propagation and a good knowledge of the damage modes developed in structures are needed in order to apply NDT with optimal efficiency. Certain authors should be consulted [1][2][3][4][5][6][7][8][9][10][11][12][13] to gain a better understanding of Lamb waves and knowledge of propagation in anisotropic composite materials. Recently, Lamb waves have become widely used for NDT applications [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies of beam reflection from planar structures have also been carried out. [5][6][7] The related problem in structural acoustics of reflection of sound from cylinders [8][9][10] has dealt with planar incident fields, where the sound wave field does not vary appreciably over the cylinder diameter. A more thorough review of this literature can be found in Ref.…”
Section: Introductionmentioning
confidence: 99%